2005
DOI: 10.1177/1534735405282361
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for and Characteristics Associated With Complementary and Alternative Medicine Use Among Adult Cancer Patients: A Systematic Review

Abstract: Reasons for and characteristics associated with CAM use among cancer patients have been studied extensively. Future CAM research among cancer patients should focus on identifying decision-making processes and building theoretical decision-making models. These can be used in the development of decisional aids for patients when confronted with the choice to use CAM as part of their cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
210
4
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(236 citation statements)
references
References 53 publications
14
210
4
8
Order By: Relevance
“…For example, in the studies carried out it is found that massage and touch therapies are preferred in Australia and Israel, herbal products and medicines are preferred in Europe and America and praying is preferred in Turkey. As a result of 52 studies that Verhoef et al reviewed in their systematic compilation, it is determined that cancer patients use CAM methods according to the religious preferences of the country they live in (Verhoef et al, 2005). In the light of these findings, it is thought that cancer patients use the methods related to the religious preferences which are frequently used in the area where they live and which they believe that they will relieve the stress and make them psychologically strong.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the studies carried out it is found that massage and touch therapies are preferred in Australia and Israel, herbal products and medicines are preferred in Europe and America and praying is preferred in Turkey. As a result of 52 studies that Verhoef et al reviewed in their systematic compilation, it is determined that cancer patients use CAM methods according to the religious preferences of the country they live in (Verhoef et al, 2005). In the light of these findings, it is thought that cancer patients use the methods related to the religious preferences which are frequently used in the area where they live and which they believe that they will relieve the stress and make them psychologically strong.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is seen that women diagnosed with gynecologic cancer use CAM frequently (Upchurch and Chyu, 2005;Akyuz et al, 2007;Amanak et al, 2013). When studies on CAM are reviewed, it is determined that most of the patients cannot explain the reason why they use CAM clearly and do not have any information on the effects/side effects of using CAM (Verhoef et al, 2005;Tokem, 2006;Kav et al, 2008). For that reason, it is stated that there is a need randomized controlled studies with high level of evidence, systematic literature reviews and meta-analyzes regarding the efficiency of CAM practices (Can, 2013).…”
Section: Use Of Complementary and Alternative Medicine In Patients Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews on the subject need up-dating and do not provide detailed information focused on CAM use in prostate cancer. [16][17][18] Currently, this makes it difficult to have confidence in assertions about the prevalence of CAM use in prostate cancer. Furthermore, a comprehensive up-to-date review would provide useful information for oncologists that could aide their communication with patients about CAM, inform the research community as to gaps and inconsistencies in this literature and possibly identify new research areas.…”
Section: Introductionmentioning
confidence: 99%
“…Predictors of CAM in Western countries, however, include being female (Molassiotis et al, 2005;Risberg et al, 2003), younger (Burstein et al, 1999;Risberg et al, 2003), more highly educated (Kao and Devine, 2000;Lerner and Kennedy, 1992), employed (Verhoef et al, 2005), professional (Downer et al, 1994), and having a higher income (Kao and Devine, 2000;McEachrane-Gross et al, 2006), while other studies showed inconsistent associations (Navo et al, 2004) or none (Tasaki et al, 2002). Although several studies report no relationship between CAM use and conventional treatment (McEachrane-Gross et al, 2006), advanced stage (Tas et al, 2005), or disease site (Fernandez et al, 1998), patients with lymphoma or cancer of the brain or CNS tend to use CAMs.…”
Section: Discussionmentioning
confidence: 99%